MULTILINGUAL EDUCATIONAL ENVIRONMENT: SIGNIFICANCE AND RESEARCH MAIN METHODS - Ermekova, A. B. (Zkatu im. Zhangirhana, 2022)
Language is a social phenomenon. His research suggests raising the consciousness of society. Multilingual environment is the basis of modernity. Due to the fact that the study of a foreign language has become more multilingual among the Kazakhs. The diversity of the nation and the people as a whole is a complex phenomenon, which is the object of research of sociolinguists. In the conditions of mass multilingualism communicative forms (dialects, dialects, various jargons, separate languages) make hierarchy of very difficult application. Some countries are based on a multilingual environment. Each language must retain its own characteristics. Therefore, learning a multilingual environment is important. Multilingual education is the core of the formation of a multicultural personality. Today, multilingual education is a necessity that allows the younger generation to move freely in the educational space, navigate the mysteries of world science and show their abilities.
Ermekova, A. B. MULTILINGUAL EDUCATIONAL ENVIRONMENT: SIGNIFICANCE AND RESEARCH MAIN METHODS / A. B. Ermekova, А. Б. Ермекова. - Текст : непосредственный // Ғылым және білім: Қазіргі көзқарас жағдайындағы ғылым мен білімді дамытудың өзекті мәселелері: ХХІІ халықаралық ғылыми-практ. конф. материалдары (12 сәуір 2022 ж.) = Наука и образование: Актуальные вопросы развития науки и образования в условиях современных вызовов: мат. ХХІІ междунар. науч.-практ. конф. (12 апреля 2022 г.) = Science and education: topical issues of the development of sciense and education in the context of modern challenges: mat. of the XXII International Scientific and Practical Conf. (12 aptil 2022). - Уральск: ЗКАТУ им. Жангир хана. - 2022. - № 2 (67) : прил. № 2. - Р. 259-266 (Uralsk).
Keywords: multilingualism; linguistics; trilingualism; language families; language composition; research methods; communication; научный журнал; зкату